An outbreak of Cutaneous Leishmaniasis in a village of district Dir, NWFP. - Rahim, Fazal; Jamal, Shiraz; Raziq, Fazal; Uzair, Muhammad; Sarwar, Bakht; Ali, Hazrat; Sherin, Muhammad (Journal of Postgraduate Medical Institute, 2011)
to study the frequency of cataneous leishmaniasis at a village inundated by sandfly. A lieshmaniasis diagnosis camp was arranged at village wattangi, district Dir. All patients with suspected cutaneous leishmaniasis having active lesion were recruited in the study. data of the patients e.g. name, age, sex and site of lesions were entered into a register. Smears were prepared from the sides of the lesions with sterile lancets, fixed with absolute alcohol, stained with Geimsa stain and examined under microscope. Out of 40 examined patients, 37 were positive for leishmania tropica (LT) bodies. The most common site involved was face and the most common age group affected was less than 10 years. The frequency of autoneuous leishmaniasis is quite high at Watangi village of distt. dir, due to infestation by sand flies, lack of medical education and low socio economic status in the are.